Stable O and C isotopes of Globorotalia inflata in sediment cores GeoB6209-2, GeoB6220-1, GeoB13862-1, GeoB6311-2, GeoB2722-1 - Jonkers, Lukas; Gopalakrishnan, Akshat; Weßel, Lea; Chiessi, Cristiano Mazur; Groeneveld, Jeroen; Monien, Patrick; Lessa, Douglas O; Morard, Raphael (In: Jonkers, L et al. (2020): Stable isotopes, counts and raw element data of Globorotalia inflata from sediment cores, Southwest Atlantic [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.922024, 2020)
Measurements were performed on groups of 3 shells in core GeoB13862-1 and on groups of 3-10 shells in the core top samples using a Thermo MAT 253plus coupled to a Kiel IV device at MARUM. Analytical precision was determined through repeat measurements of an in-house carbonate standard (Solnhofen limestone), which was calibrated to the NBS 19 calcite standard, and amounted to 0.06 and 0.03 ‰ for δ18O and δ13C, respectively.